The use of Rasch competency bands for reporting criterion-referenced feedback and curriculum-standards attainment - Combrinck, Celeste; Schoeman, Vanessa; Maree, David (Faculty of Education, University of the Free State, 2016)
This study describes how criterion-referenced feedback was produced from English language, mathematics and natural sciences monitoring assessments. The assessments were designed for grades 8 to 11 to give an overall indication of curriculum-standards attained in a given subject over the course of a year (N=1113). The Rasch Item Map method was used to set cut-scores for the Rasch competency bands, after which subject specialists examined the items in each band. Based on the content and difficulty of the items, descriptions for the proficiency levels were generated. Learner reports described each individual’s current proficiency level in a subject area as well as the subsequent level to be attained. This article shows how the Rasch Item Map method can be used to align assessments and curriculum-standards, which facilitates reporting learner performance in terms of criterion-referenced feedback and empowers learners, teachers and parents to focus on subject content and competencies.
Keywords: Rasch competency bands; Proficiency levels; Criterion-referenced feedback; Rasch Item Map method; Curriculum standards; Reporting learner performance